The Effect of Entrepreneurship Education, Financial Literacy, Family Environment, and Love of Money on the Entrepreneurial Interest of Indigenous Papuan Students - Westim Ratang; Gabriel Yusuf; Adhi Nugroho (Westscience Press, 2026)
The high unemployment rate in Papua underscores the need to foster entrepreneurial interest among young people, particularly Indigenous Papuan (Orang Asli Papua/OAP) students. This study examines the effect of entrepreneurship education, financial literacy, family environment, and love of money on the entrepreneurial interest of OAP students in the Department of Management, Faculty of Economics and Business, Cenderawasih University. A quantitative approach with an associative-causal design was employed. The sample comprised 65 respondents selected through purposive sampling, namely OAP students who had taken the entrepreneurship course. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression. The results show that entrepreneurship education (β = 0.512) and love of money (β = 0.492) have a significant positive effect on entrepreneurial interest, whereas financial literacy has a significant negative effect (β = -0.357). Family environment (β = 0.067) has no significant effect. Simultaneously, the four variables affect entrepreneurial interest (F = 13.244; ρ = 0.000), with a contribution of R² = 46.9%, while 53.1% is explained by other variables outside the study. These findings indicate that hands-on entrepreneurial learning and an internal orientation toward money are stronger determinants of OAP students' entrepreneurial interest than the family environment.